PROM1 gene variations in Brazilian patients with macular dystrophy. (2nd January 2017) - Salles, Mariana Vallim; Motta, Fabiana Louise; Dias da Silva, Elton; Varela Lima Teixeira, Patricia; Antunes Costa, Kárita; Filippelli-Silva, Rafael; Martin, Renan; Pesquero, João Bosco; Ferraz Sallum, Juliana Maria
ABSTRACT: Background : Although the pathogenicity of the prominin-1 ( PROM1 ) gene has already been described as associated with autosomal dominant Stargardt disease, little is known about sequence variations in this gene. Purpose : The aim of this study was to evaluate PROM1 gene sequence variations in patients with macular dystrophy. Material and methods : This retrospective study evaluated variations in the PROM1 gene detected by next-generation sequencing test in patients with macular dystrophy and Stargardt disease. Results : Of 25 medical records of patients with Stargardt disease, three records of patients with PROM1 gene sequence variations were selected for the study. The p.Asp776Val and p.Asp829Asn variants were detected in cases 1 and 2, respectively, and predicted to be pathogenic; they were probably responsible for macular dystrophy in these patients. Case 3 showed a p.Ala643Gly variant in the PROM1 gene and a single variation in the ABCA4 gene, but molecular testing results were inconclusive. Conclusions : In cases of Stargardt disease, where molecular testing results are inconclusive for pathogenic variations in the ABCA4 gene, variations in the PROM1 gene may occur and be considered responsible for the disease in the molecular analysis. This study described three cases in which variations in PROM1 gene may play a role in the pathogenesis of macular dystrophy or be associated with both autosomal recessive and autosomal dominant inheritance.